A High‐Throughput Process for the Solid‐Phase Purification of Synthetic DNA Sequences. Issue 1 (19th June 2017) - Grajkowski, Andrzej; Cieślak, Jacek; Beaucage, Serge L.
Abstract: An efficient process for the purification of synthetic phosphorothioate and native DNA sequences is presented. The process is based on the use of an aminopropylated silica gel support functionalized with aminooxyalkyl functions to enable capture of DNA sequences through an oximation reaction with the keto function of a linker conjugated to the 5′‐terminus of DNA sequences. Deoxyribonucleoside phosphoramidites carrying this linker, as a 5′‐hydroxyl protecting group, have been synthesized for incorporation into DNA sequences during the last coupling step of a standard solid‐phase synthesis protocol executed on a controlled pore glass (CPG) support. Solid‐phase capture of the nucleobase‐ and phosphate‐deprotected DNA sequences released from the CPG support is demonstrated to proceed near quantitatively. Shorter than full‐length DNA sequences are first washed away from the capture support; the solid‐phase purified DNA sequences are then released from this support upon reaction with tetra‐ n ‐butylammonium fluoride in dry dimethylsulfoxide (DMSO) and precipitated in tetrahydrofuran (THF). The purity of solid‐phase‐purified DNA sequences exceeds 98%. The simulated high‐throughput and scalability features of the solid‐phase purification process are demonstrated without sacrificing purity of the DNA sequences. © 2017 by John Wiley & Sons, Inc.